PENGARUH BOPO, FDR DAN NPF TERHADAP PROFITABILITAS (ROA) PADA BANK SYARIAH PERIODE 2009-2019 - Ahmad Fauzul Hakim Hasibuan; Falahuddin Falahuddin Falahuddin; Hail Ulva (LPPM, 2021)
This study aims to determine the effect of operational costs on the operational income, financing to deposit ratio, and non-performing financing to profitability (ROA) in Islamic banks during 2009-2019. The data used in this study are secondary data sourced from Islamic banking financial statements accessed on the official website of the Financial Services Authority with monthly data from January 2009 to December 2019. This study used is a quantitative approach with VAR (Vector Auto-Regressive) analysis, consisting of stationarity test, optimal lag test, VAR model stability test, Granger causality test, impulse response function test, and variance decomposition test. Based on the results of this study, it concludes that NPF is more dominant in influencing profitability (ROA) in the short and long term. The results of the Granger causality test show that all variables have a causal relationship with each other, meaning that each variable has a causal relationship with each other and has a two-way relationship with other variables. The variables used in this study are BOPO, FDR, NPF. It is hoped that the next researcher can use more not only Islamic bank financial performance variables but also income, inflation, interest rates, and investment variables that are included as determinants of ROA levels in Islamic banking in Indonesia. Keywords: BOPO, FDR, NPF, ROA, VAR